Efektivitas Logoterapi untuk Meningkatkan Kebermaknaan Hidup pada Lansia di UPT Dinas Sosial Pematang Siantar - Fajrah, Fadhilla (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The increase in the number of older adults every year is an important concern, especially regarding the welfare of the elderly. The older a person gets, the more they need a place to take shelter and get love, especially from family. Not all elderly people are lucky enough to be able to live with their families and pay attention to their welfare. Many elderly people experience a decrease in their quality of life while staying at the social service for the elderly and even lose the meaning of their lives. Meaning of life is easier to find and higher level when in a pleasant situation. But finding the meaning of life can also be in conditions of suffering or suffering, such as being in a social service or nursing home. This encourages researchers to determine the effectiveness of logotherapy. Logotherapy is also often given as an alternative to psychotherapy for various problems faced by the elderly. The purpose of this study was to see the effectiveness of logotherapy in increasing the meaning of life in the elderly. This study uses a quantitative method with a quasi-experimental design. The participants in this study were 12 elderly people in the social service of PematangSiantar who were divided into two groups (experimental and control groups). The results of this study showed that logotherapy was significantly effective in increasing the meaningfulness of life in the elderly with p = 0.036 or <0.05. The effect of logotherapy on the meaning of life in the elderly also has a large effect, namely r = -0.89. These results indicate that logotherapy is effective in increasing the meaning of life for the elderly.